Sustainable garden pea cultivation: a comprehensive evaluation of organic, inorganic, and bio-fertilizer impacts on productivity, quality and nutrient dynamics - Quddus, Abdul; Ahmed, Razu; Khan, Shihab Uddine; Purnota, Samia Jahan; Islam, Torikul; Sultana, Nazneen Ara; Aktar, Shamima; Fahad, Zoheb Hasan; Rahimi, Mehdi; Uddin, Kamal (Springer Science and Business Media Deutschland, 2026)
Efficient nutrient management is crucial for profitable garden pea (Pisum sativum L.) production. A field study evaluates the practical consequences of bio-fertilizer, organic and inorganic fertilizer application strategies on garden pea productivity, quality, nutrient uptake, efficiency and economic viability. Utilizing a Randomized Complete Block Design with seven treatments replicated three times. Treatments were T1 = Control, T2 = Recommended of N-P-K-S-Zn-B at 60–25-40–10-3–2 kg ha−1, T3 = 1.25 t ha−1 vermicompost (VC)+ Rhizobium inoculant (50 g/kg seed) + 75% of NPKSZnB, T4 = 1.25 t ha−1 VC+1.40 t ha−1 cowdung (CD)+ Rhizobium inoculant (50 g/kg seed)+ 50% of NPKSZnB, T5 = 1.20 t ha−1 poultry manure (PM)+1.40 t ha−1 CD+ Rhizobium inoculant (50 g/kg seed) +50% of NPKSZnB, T6 = 1.25 t ha−1 VC+1.20 t ha−1 PM+ Rhizobium inoculant (50 g/kg seed) + 50% of NPKSZnB and T7 = 1.40 t ha−1 CD+ Rhizobium inoculant (50 g/kg seed)+75% of NPKSZnB. Treatment T3 produced the highest green pod (10.7 t ha−1) and seed (2.46 t ha−1) yields, attributed to more pods per plant, larger pods, and heavier seeds. Economically, T3 demonstrated substantial increments over control, boosting gross returns by 48.9% and the BCR by 22.3% for green pods. For dry seeds, T3 increased gross returns by 42.5% and BCR by 16.8%.Treatment T3 resulted in the highest levels of vitamin C (42.2 mg/100 g), protein (22.1%), and nodulation (34.2). Moreover, this treatment improved nutrient acquisition, uptake, and recovery efficiency. Results suggest that combined application of 1.25 t ha−1 vermicompost+Rhizobium inoculant+ 75% of NPKSZnB fertilizer is highly effective for enhancing garden pea productivity and quality, while also promoting sustainable soil health and environmental benefits.